Effect of water content on the properties of OPS concrete containing palm oil fuel ash - Nur Afiqah Fatihah, Hamidon (2012)
Oil palm shell (OPS) and palm oil fuel ash (POFA) generated as by product from Malaysian palm oil mills has been disposed at landfill in increasing quantity thus creating environmental pollution. Steps taken to incorporate these waste materials in concrete production would be able to reduce the amount of waste disposed at landfill. This thesis presents an experimental study on the performance of OPS concrete consisting POFA as partial sand replacement material at different water cement ratio. OPS concrete has been considered as control mix. Another mix is OPS concrete consisting five percent of POFA. A total of 96 concrete cubes have been tested in this study. The performance of OPS POFA concrete in term of workability, compressive strength, and moisture absorption when different water cement ratio used have been investigated. The results demonstrate that the workability for OPS POFA samples increase as the water cement ratio increased. Increase in the water cement ratio added causes reduction in the compressive strength and water absorption of OPS POFA concrete.